HUBUNGAN PENGGUNAAN MEDIA PEMBELAJARAN DENGAN MINAT BELAJAR SISWA PADA MATA PELAJARAN FIQIH KELAS IV MI AL MADANI TAJUR HALANG KAB. BOGOR - Silmi Siti Rabiatul Adawiyah; Muhammad Fahri (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2018)
This study aims to (1) know the use of audiovisual learning media in the subjects of Fiqh class IV in MI Al-Madani, (2) to know students' interest in the subject of Fiqh class IV in MI-Al-Madani, (3) to know the relationship of usage media learning with interest in student learning subject of Fiqh class IV in MI Al-Madani. In this study using correlation method, this correlation method is part of quantitative research with field research type (field research). In this study the researchers used a sample of all populations of 95 students. Instruments used in this study are: observation, questionnaires, and documentation. Based on data analysis, the research result can be concluded that: (1) it can be seen that the use of learning media in the subject of Fiqh class IV in MI Al-Madani got the interpretation of good enough value with the average respondent answer SL